The conventional media's political economy practices in the media convergence era: Case study of labor commodification in TV industry - Estavita Chantik Pembayun; Ardian Indro Yuwono (Informasi, 2023)
Technological developments provide benefits for the society in receiving information and entertainment. This has resulted many innovations made by the communication media industry players, one of which is NET. TV by conducting media convergence. Media convergence is a consequence caused by technological developments, which then affects competition in the media industry. Media convergence is gaining momentum in the communications industry, where digital technology is being used more than conventional one. Under the auspices of PT Net Visi Media, NET. TV has now looked at YouTube and over-the-top digital platforms. By looking at the transitions, this research was conducted with a critical paradigm by mapping the problems that occur related to vertical power relations, based on political economy theory of communication media by Vincent Mosco. Interview with NET. TV production team became the primary data, which was then analyzed descriptively. According to the characteristics coined by Vincent Mosco as an analytical tool, the result is NET. TV performs absolute and relative labor commodification during media convergence. Where the Tonight Show Premiere and Match Island production teams are required to be multitasking and work overtime without being paid.